2012
DOI: 10.1142/s2010132512500150
|View full text |Cite
|
Sign up to set email alerts
|

Modeling and Verification of Heat and Moisture Transfer in an Enthalpy Exchanger Made of Paper Membrane

Abstract: In this study, heat and moisture transfer model of an enthalpy exchanger is proposed. With separately measured sorption constant and diffusion coefficient, the model predicts the heat and moisture transfer effectiveness of an enthalpy exchanger. Two sample enthalpy exchangers were tested at a KS condition to verify the model. The model predicts the heat transfer effectiveness within 4%, and the moisture transfer effectiveness within 10%. Pressure drop is predicted within 6%. The spacer fin efficiency for heat … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
1
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(6 citation statements)
references
References 24 publications
1
1
0
Order By: Relevance
“…That tree' branch presents the minority classes that represents the most considerable portion of the farms, concerning the productivity index. Such results agree with the current literature (Moro et al, 2005;Rodrigues et al, 2011); however, the influence of the rearing conditions and health status might not be neglected (Lee et al, 2012;Bhadauria et al, 2017;De Jong and Van Riel, 2020).…”
Section: Data Mining Resultssupporting
confidence: 92%
See 1 more Smart Citation
“…That tree' branch presents the minority classes that represents the most considerable portion of the farms, concerning the productivity index. Such results agree with the current literature (Moro et al, 2005;Rodrigues et al, 2011); however, the influence of the rearing conditions and health status might not be neglected (Lee et al, 2012;Bhadauria et al, 2017;De Jong and Van Riel, 2020).…”
Section: Data Mining Resultssupporting
confidence: 92%
“…According to data mining methodology, the analysis was divided into five distinct phases: 1) Understanding the domain of knowledge to which the study refers; 2) Knowledge and understanding of the database for this domain; 3) Data preparation (cleaning, construction, selection, integration, and formatting); 4) Modeling; 5) Evaluation of results, allowing for reconsiderations and cyclical reassessments (Chapman et al, 2000). The trees' output format is characterized by a relatively fast construction process and straightforward interpretation of a final model (Lee et al, 2012). They are based on an 'If-Then' rules approach to learning from a set of independent observations.…”
Section: Introductionmentioning
confidence: 99%
“…Lee et al [4] enhanced the diffusivity of paper by impregnating it with lithium chloride (LiCl). The reported values of the moisture diffusivity ranged from 1.8 × 10 −11 m 2 /s to 6.0 × 10 −11 m 2 /s and in another study, it was found to be 3.8 × 10 −11 m 2 /s [5].…”
Section: Introductionmentioning
confidence: 89%
“…The more hydrophilic a material, the higher the latent effectiveness that can be expected. Lee et al [5] investigated the influence of airflow, humidity, temperature, and fin properties on heat and latent effectiveness. The values of the fin efficiencies for heat transfer were between 0.11 and 0.13.…”
Section: Mathematical Model Of the Exchangermentioning
confidence: 99%
See 1 more Smart Citation